From Consultation to Collaboration: Harnessing Stakeholder Involvement for Innovation in Higher Education - Dangarembwa George (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
This chapter explores the shift from traditional consultation to active collaboration in higher education to foster innovation and adapt to evolving industry and societal needs. Traditionally, higher education institutions have engaged stakeholders through various consultation mechanisms (i.e., surveys, advisory boards, etc.). While valuable, these mechanisms often fail to fully leverage stakeholder expertise in shaping institutional strategy and curriculum. This chapter argues that true innovation in higher education requires moving towards a more collaborative model, where stakeholders co-create solutions, share knowledge and engage in decision making. Using document analysis, case studies were drawn from Google Scholar, Web of Science, Scopus and JSTOR to articulate the importance of collaboration, the evolution of stakeholder involvement in higher education, alignment of the curriculum with industry needs, interdisciplinary approaches to problem solving and accelerated innovation. It also looks at key strategies for fostering collaboration, such as creating partnerships, incorporating diverse stakeholder feedback and leveraging digital platforms. This chapter also emphasises empowering stakeholders to take an active role in educating pupils about the intricacies of contemporary human capital.